A photocaged, cyclopropene-containing analog of the amino acid neurotransmitter glutamate. Issue 51 (21st December 2016) - Kumar, Pratik; Shukhman, David; Laughlin, Scott T.
Graphical abstract: Highlights: The bio-orthogonal chemistry toolbox has not yet been applied to the study of neurotransmitters. The synthesis of a cyclopropene-modified analog of the neurotransmitter glutamate is described. Appending a light-cleavable group to the glutamate analog enables potential deployment in vivo . Abstract: Substituted cyclopropenes serve as compact biorthogonal appendages that enable analysis of biomolecules in complex systems. Neurotransmitters, a chemically diverse group of biomolecules that control neuron excitation and inhibition, are not among the systems that have been studied using biorthogonal chemistry. Here we describe the synthesis of cyclopropene-containing analogs of the excitatory amino acid neurotransmitter glutamate starting from a Garner's aldehyde-derived alkyne. The deprotected cyclopropene glutamate was stable in solution but decomposed upon concentration. Appending a light-cleavable group improved the stability of the cyclopropene while simultaneously caging the neurotransmitter. This strategy has the potential to permit deployment of cyclopropene-modified glutamate as a bioorthogonal probe of the neurotransmitter glutamate in vivo with spatiotemporal precision.